Highly efficient detection of ciprofloxacin with a self-powered sensing device based on a Au NPs/g-C3N4 micron tube and a 3D Ni-doped ZnIn2S4 thin film. Issue 1 (9th December 2022) - Ouyang, Xilian; Feng, Chengyang; Zhu, Xu; Liao, Yibo; Fan, Xinya; Zhou, Zheping; Zhang, Ziling; Tang, Lin
Abstract : A self-powered double-photoelectrode sensing device is proposed for the rapid quantification of ciprofloxacin. Abstract : As a second-generation fluoroquinolone antibiotic, ciprofloxacin (CIP) has been widely used in recent years, which allows it enter the water environment and food chain through various ways, causing serious harm to human health and the ecological environment. It is urgent to explore ultrasensitive and maneuverable monitoring methods to solve the environmental pollution caused by excessive use of CIP. In this study, a self-powered sensing device was fabricated based on a photoelectrochemical (PEC) system and 3D printing technology, which could generate electrical output to provide a sensing signal under photoirradiation, without an external power source, displaying highly efficient detection of CIP. In this system, n-type Au nanoparticles/graphite carbon nitride (g-C3 N4 ) micron tube-modified fluorine tin oxide (FTO) conductive glass slides served as the photoanode for the oxidation of CIP under photoirradiation while p-type Ni-doped ZnIn2 S4 film-modified FTO was employed as the cathode for the reduction of dissolved oxygen. A thiolated CIP binding aptamer was loaded on the surface of the photoanode to ensure selectivity. Combining photoactive materials and the aptamer, the as-obtained sensing platform can achieve the sensitive and specific recognition of CIP under complex environmental conditions. The open-circuit voltage (OCP) was sensitive to CIP in a wide concentration range (0.2–3840 ng mL −1 ) and had a low detection limit at 0.03 ng mL −1 . This strategy paves the way to a simple approach for the determination of CIP in sewage and several commercial pure milk samples.